Melatonin attenuates acute pancreatitis-associated lung injury in rats by modulating interleukin 22 - Huai, Jia-Ping (World journal of gastroenterology : WJG, 2012)
AIM： To investigate whether therapeutic treatment with melatonin could protect rats against acute pan- creatitis and its associated lung injury. METHODS： Seventy-two male Sprague-Dawley rats were randomly divided into three groups： the sham op- eration （SO）, severe acute pancreatitis （SAP）, and mel- atonin treatment （MT） groups. Acute pancreatitis was induced by infusion of 1 mL/kg of sodium taurocholate （4% solution） into the biliopancreatic duct. Melatonin （50 mg/kg） was administered 30 min before pancre- atitis was induced, and the severity of pancreatic and pulmonary injuries was evaluated 1, 4 and 8 h after induction. Serum samples were collected to measure amylase activities, and lung tissues were removed to measure levels of mRNAs encoding interleukin 22 （IL-22） and T helper cell 22 （Th22）, as well as levels of IL-22.ing IL-22 and Th22 were significantly higher （P 〈 0.001） in the MT group than in the SAP group （0.526 ± 0.143 vs 0.156 ± 0.027, respectively, here and throughout, after 1 h; 0.489 ± 0.150 vs 0.113 ± 0.014 after 4 h; 0.524 ± 0.168 vs 0.069 ± 0.013 after 8 h, 0.378 ± 0.134 vs 0.122 ± 0.015 after 1 h; 0.205 ± 0.041 vs 0.076 ± 0.019 after 4 h; 0.302 ± 0.108 vs 0.045 ± 0.013 after 8 h, respectively） and significantly lower （P 〈 0.001） in the SAP group than in the SO group （0.156 ± 0.027 vs 1.000 ± 0.010 after 1 h; 0.113 ± 0.014 vs 1.041 ± 0.235 after 4 h; 0.069 ± 0.013 vs 1.110 ± 0.213 after 8 h, 0.122 ± 0.015 vs 1.000 ± 0.188 after 1 h; 0.076 ± 0.019 vs 0.899 ± 0.125 after 4 h; 0.045 ± 0.013 vs 0.991 ± 0.222 after 8 h, respectively）. The mean pathologi- cal scores for pancreatic tissues in the MT group were significantly higher （P 〈 0.01） than those for samples in the SO group （1.088 ± 0.187 vs 0.488 ± 0.183 after 1 h, 2.450 ± 0.212 vs 0.469 ± 0.242 after 4 h; 4.994 ± 0.184 vs 0.513 ± 0.210 after 8 h）, but were significantly lower （P 〈 0.01） than those for samples in the SAP group at each time point （1.088 ± 0.187 vs 1.969 ± 0.290 after 1 h; 2.450 ± 0.212 vs 3.344 ± 0.386 after 4 h; 4.994 ± 0.184 vs 6.981 ± 0.301 after 8 h）. The severity of SAP increased significantly （P 〈 0.01） over time in the SAP group （1.088 ± 0.187 vs 2.450 ± 0.212 between 1 h and 4 h after inducing pancreatitis; and 2.450 ± 0.212 vs 4.994 ± 0.184 between 4 and 8 h after inducing pan- creatitis）. CONCLUSION： Melatonin protects rats against acute pancreatitis-associated lung injury, probably through the upregulation of IL-22 and Th22, which increases the innate immunity of tissue cells and enhances their regeneration.